UTILISATION OF VEGETABLE LEAVES FOR CARP PRODUCTION - ROY, A. K.; RAI, S. P.; DATTA, A. K.; DAS, C. R.; GHOSH, J. K. (Journal of Indian Fisheries Association, 2015)
The results of two sets of experiments on mono-culture of grass carp(Ctenopharyngodon idella) and mixed culture of carps (grass carp 50 :catla 20 : rohu 15 : mrigal 15) fed exclusively with vegetable leaves arereported. The experiments were conducted with two replicates each in0.02 ha ponds of Wastewater Aquaculture Division of the Central Instituteof Freshwater Aquaculture, Rahara during 1991-93.Monoculture of grass carp stocked @ 1000/ha demonstrated an averagenet production of 21.0 kg/ 0.02 ha/8 months (1501 kglha/yr). Mixed cultureof carps stocked @ 5000 /ha recorded an average net production of 22.5kg/0.02 ha/8 months (1903.7 kg!ha/yr). Field studies revealed that waterbind weed (Ipomoea aquatica) is the most preferred feed of grass carpamongst vegetable leaves followed by amaranths (Amaranthus gangeticusand Amaranthus viridis), cauliflower (Brassica oleracia var. votrytis)and cabbage (Brassica oleracia var. capitata) leaves. Through selectionof highly productive leaf vegetables and suitable crop planning on fallowfish pond dykes, round the year feeding programme of grass carp hasbeen explored. Recycling of sewage .effluent for vegetable production andutilisation of vegetable leaves for fish production is considered an idealway of integrated resource management for low cost production.